Conversion of boiler houses to alternative fuel - E. N. Makeeva; E. R. Zvereva; O. Yu. Morozova (Известия высших учебных заведений: Проблемы энергетики, 2024)
THE PURPOSE. To justify the need to transfer boiler houses from fuel oil to furnace domestic fuel.   METHODS. Comparative studies of the main indicators of the quality of fuel oil and domestic heating oil (DHO) (heat of combustion, kinematic viscosity, flash point, pour point, ash content, humidity, sulfur content) were carried out. The environmental parameters of pollutants formed during the combustion of fuel oil and domestic stove fuel are calculated and compared with the values regulated by the EkoNiP 17.01.06-001-2017 "Environmental protection and nature management. Requirements of environmental safety" and TCU 17.02-XX-2019 "Environmental protection and nature management".   RESULTS. As a result of comparative studies of the main indicators of the quality of fuel oil and furnace household fuel (PBT), it was shown that combustion in PBT boilers in comparison with fuel oil is preferable in terms of environmental consequences in terms of emissions into the atmosphere. As a result of the comparative analysis, it was found that during the transition from fuel oil to furnace household fuel, compliance with the basic environmental standards regulated by these regulatory documents is ensured by reducing by 70 times the amount of sulfur dioxide released into the atmospheric air during 10 days of burning furnace household fuel, as well as reducing the concentration of this type of emission by 72.5 times. When switching from fuel oil to furnace household fuel, pollution and equipment wear are also reduced due to the ash content index for furnace household fuel being 7 times lower than that of fuel oil, as well as a 2-fold reduction in the formation of soot and 70-fold reduction in sulfur dioxide during ten-day use of a new reserve type of fuel.   CONCLUSION. Thus, as a result of experimental and calculated studies, it was shown that combustion in DHO boilers in comparison with fuel oil is preferable in terms of environmental consequences in terms of emissions into the atmosphere, reducing corrosion, stopping boilers for repairs, reducing fuel heating costs to facilitate transportation, reducing steam and fuel costs. When switching from fuel oil to furnace household fuel, pollution and equipment wear are also reduced due to the ash content index for furnace household fuel that is 7 times lower than that of fuel oil, as well as a 2-fold reduction in the formation of soot and 70-fold reduction in sulfur dioxide during ten-day use of a new reserve type of fuel.